The feasibility of using exoskeletal‐assisted walking with epidural stimulation: a case report study. Issue 2 (5th February 2020) - Gorgey, Ashraf S.; Gill, Satinder; Holman, Matthew E.; Davis, John C.; Atri, Roozbeh; Bai, Ou; Goetz, Lance; Lester, Denise L.; Trainer, Robert; Lavis, Timothy D.
Abstract: Spinal cord epidural stimulation (SCES) exhibits a rehabilitation potential of restoring locomotion in individuals with spinal cord injury (SCI). However, this is linked to an intensive rehabilitation locomotion approach, which is impractical to apply among a large clinical SCI population. We, hereby, propose a rehabilitation approach of using SCES to enhance motor control during exoskeletal‐assisted walking (EAW). After 24 sessions (12 weeks) of EAW swing assistance decreased from 100% to 35% in a person with C7 complete SCI. This was accompanied by 573 unassisted steps (50% of the total number of steps). Electromyographic pattern improved during EAW, reflecting the subject's ability to rhythmically activate paralyzed muscles. Rate perceived exertion increased during EAW with SCES compared to stepping without SCES. These preliminary findings suggest that using SCES with EAW may be a feasible rehabilitation approach for persons with SCI.